(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Friction stir welding (FSW) is solid state joining process with more advantages than that of fusion welding. Nylon -6 is one of the engineering plastics used widely in various industrial applications. The main aim of this research work is to investigate the effect of tool rotational speed and tool traversing speed on the mechanical and microstructural properties of the nylon-6 butt welded joints made by FSW. The FSW process was performed in a computer numerically controlled (CNC) vertical milling machine using a cylindrical tool with threaded pin made of heat treated high carbon high chromium (HCHCr) steel. The tensile testing and microscopic examinations were carried out to study the mechanical and microstructural properties of the welded joints. In visual inspection, it is observed that the excessive flashes are observed on either sides of the weld line in all cases. From the results, it is observed that the maximum tensile properties are achieved in a joint made which is approximately 18% and 26% of the parent material’s ultimate tensile strength (UTS) and yield strength (YS) respectively with the tool rotational speed 1200 rpm and the tool traversing speed of 30 mm/min within the experimented process parameters. Overall, the tensile properties of the welded joints made using the experimented process parameters are very much lower than the parent material.